Screening of native microalgae species for carbon fixation at the vicinity of Malaysian coal‑fired power plant - Yahya, Liyana; Harun, Mohd Razif; Abdullah, Luqman Chuah (Springer Nature, 2020)
Global warming has become a serious issue nowadays as the trend of CO2 emission is increasing by years. In Malaysia, the electricity and energy sector contributed a significant amount to the nation’s CO2 emission due to fossil fuel use. Many research works have been carried out to mitigate this issue, including carbon capture and utilization (CCUS) technology and biological carbon fixation by microalgae. This study makes a preliminary effort to screen native microalgae species in the Malaysian coal-fired power plant’s surrounding towards carbon fixation ability. Three dominant species, including Nannochloropsis sp., Tetraselmis sp., and Isochrysis sp. were identified and tested in the laboratory under ambient and pure CO2 condition to assess their growth and CO2 fixation ability. The results indicate Isochrysis sp. as the superior carbon fixer against other species. In continuation, the optimization study using Response Surface Methodology (RSM) was carried out to optimize the operating conditions of Isochrysis sp. using a customized lab-scale photobioreactor under simulated flue gas exposure. This species was further acclimatized and tested under actual flue gas generated by the power plant. Isochrysis sp. had shown its capability as a carbon fixer with CO2 fixation rate of 0.35 gCO2/L day under actual coal-fired flue gas exposure after cycles of acclimatization phase. This work is the first to demonstrate indigenous microalgae species' ability as a carbon fixer under Malaysian coal-fired flue gas exposure. Thus, the findings shall be useful in exploring the microalgae potential as a biological agent for carbon emission mitigation from power plants more sustainably.